Genetic and Management Effects on Barley Yield and Phenology in the Mediterranean Basin - Cammarano, Davide; Ronga, Domenico; Francia, Enrico; Akar, Taner; Al-Yassin, Adnan; Benbelkacem, Abdelkader; Grando, Stefania; Romagosa, Ignacio; Stanca, Antonio Michele; Pecchioni, Nicola (Frontiers in Plant Science, 2021)
Heading time in barley is considered a key developmental stage controlling adaptation to the environment and it affects grain yield; with combination of agronomy (planting dates) and genetics being some of the determinants of adaptation to environmental conditions in order to escape late frost, heat, and terminal drought stresses. The objectives of this study are i) to apply a gene-based characterization of one hundred and eighteen barley doubled haploid recombinants for vernalization, photoperiod and earliness per se; ii) use such information to quantify the optimal combination of genotype/sowing date that escapes extreme weather events; and ii) how water and nitrogen management impact on grain yield. The doubled haploid barley genotypes with different allelic combinations for vernalization, photoperiod and earliness per se were grown in eight locations across the Mediterranean basin. This information was linked with a crop growth model parameters. The photoperiod and earliness per se alleles modify the length of the phenological cycle, and this is more evident in combination with the recessive allele of the vernalization gene VRN-H2. In hot environments such as Algeria, Syria and Jordan early sowing dates (30-Oct, 15-Dec) would be chosen to minimize the risk of exposing barley to heat stress. To maintain higher yields in the Mediterranean basin, barley breeding activities should focus on allelic combinations that have recessive VRN-H2 and EPS2 genes, since the risk of cold stress is much lower than the one represented by heat stress.